O-132 Is there an association between sDF index and serum testosterone in human follicle stimulating hormone alfa (r-hFSH alfa) treated males with idiopathic infertility?. (30th June 2022) - Spaggiari, G; Lispi, M; Drakopoulos, P; Simoni, M; Santi, D
Abstract: Study question: Is there correlation between testosterone serum levels and sperm DNA fragmentation (sDF) index before and after follicle-stimulating hormone (FSH) administration in male idiopathic infertility? Summary answer: Correlation between testosterone and sDF was highlighted for the first time in FSH-treated men. Significant amelioration of conventional semen parameters and sDF index were confirmed. What is known already: Testicular overstimulation is the yearned therapeutic goal when exogenous FSH is empirically administered in male idiopathic infertility. Although a robust physiological rationale theoretically supports the FSH use in male idiopathic infertility, useful markers to evaluate its efficacy are still far to be identified. Whether pregnancy outcomes remain the expected valuable endpoint for couple infertility treatment, the identification of reliable, and possibly early, markers of therapeutic response to FSH in males is mandatory. Randomized controlled clinical trials (RCTs) on this topic focused, as main outcomes of FSH treatment effectiveness, on testicular seminiferous component, not considering involvement of testosterone-secreting compartment. Study design, size, duration: A retrospective post-hoc analysis of raw data extracted from two RCTs in which 148 idiopathic infertile men were treated with FSH. Participants/materials, setting, methods: A retrospective post-hoc re-analysis was performed on raw data of RCTs in which idiopathic infertile men were treated with FSH and both testosterone serum levels and sDF were reported among primary and/or secondary endpoints. Additional data regarding couple infertility history, age, anthropometric variables, FSH treatment scheme and semen variables were included in a single dataset. Data were evaluated by logistic regression analyses. Main results and the role of chance: Two RCTs were included accounting for 148 patients (median age 37, 25-52 years).  After three months of FSH administration, a significant increase was observed in FSH levels (p < 0.001), inhibin B (p = 0.012), sperm concentration (p = 0.003), total sperm number (p = 0.021), progressive motility (p < 0.001) and normal sperm morphology (p < 0.001). Moreover, an overall sDF index reduction was confirmed after treatment (19.3±9.4 versus 16.4±6.8, p = 0.002). SDF was found significantly inversely related to sperm concentration both at baseline and after FSH treatment (Rho -0.325, p < 0.001 and Rho -0.316, p = 0.001, respectively). Interestingly, sDF index after treatment showed a significant inverse correlation with testosterone serum levels (Rho -0.327, p = 0.002). Multivariate stepwise linear regression analyses using sDF index as dependent variable identified testosterone as a predictor for sDF index change (p = 0.005). Similarly, logistic regression analysis highlighted testosterone and SHBG levels as predictive of sDF reduction after FSH administration (p = 0.043 and p = 0.005, respectively). Combining raw data of published RCTs investigating FSH administration to idiopathic infertile men, a significant amelioration of conventional semen parameters together with a reduction in sDF were confirmed. Intriguingly, a potential correlation between serum testosterone and sDF was highlighted for the first time. Limitations, reasons for caution: Since the analysis was performed on raw data obtained in previous RCTs, heterogeneity among patients enrolled and evaluated should be considered interpreting these results. Moreover, a real and accurate evaluation of intratesticular testosterone levels, rather than serum levels should be more informative to the objective of the study. Wider implications of the findings: The highlighted significant correlation between testosterone serum levels and sDF is opening a completely unexplored field in the possibility to identify early predictors of FSH therapy response in male idiopathic infertility. Trial registration number: Not applicable